Older Adults’ Perception of the Impact COVID-19 Pandemic - Brito, I.; Almeida, J.; Alves, R.; Fähr-Abreu, B.; Neves, A. C.; Justo-Henriques, S.; Bobrowicz-Campos, E. (XIX PhD Meeting in Psychology “Imagining the (im)possible: the role of psychology in linking past, present and future challenges", 2024)
Older adults have been particularly affected by the COVID-19 pandemic and quarantine measures. To understand the impact of both on overall functioning of this population, a mixed-method observational study was conducted (ClinicalTrials.gov ID: NCT05379426). This communication, resulting from the work developed within the ANEP’s Internship in collaboration with LAPSO, aims to present partial data from this study, namely those collected among participants benefitting from home support services. Twenty-seven participants (52% female, median age of 81 years, mostly with 3-4 years of schooling) took part in a semi-structured interview, completed the Center for Epidemiologic Studies Depression Scale and the Geriatric Anxiety Inventory, and provided data on their pre-pandemic health condition. The interviews were audio-recorded, transcribed verbatim and analyzed based on an inductive approach. Quantitative and clinical data were subjected to descriptive analyses. Two main categories were identified: changes in daily routines and emotional impact reflected, principally, through recalls of fears, concerns, and anxiety over the COVID-19. Qualitative data were consistent with questionnaires-based data, which demonstrated the high prevalence of clinically significant depressive and anxiety symptoms. Clinical data analyses showed that these symptoms were not due to pre-pandemic health condition. In a future similar situation, we recommend an easier access to trustworthy information for older adults, explaining why certain measures are being taken and their importance for their health and safety. Moreover, we advocate for technological interventions that can help older adults keep contact with their families, and emotional support, which is an important key to assist and relieve those in pain.